Products and Services In Sharia Banking - Saprida Saprida; Choiriyah Choiriyah; Emilia Sari (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
Islamic banks are banks that in their activities, both in raising funds and in the context of distributing funds, provide and charge rewards based on sharia principles, namely buying and selling and profit-sharing. The purpose of this study is to find out how the products and services in Islamic banking and how the operational principles of Islamic banking. This research uses a descriptive survey method with qualitative data analysis. The data collection technique used is the method of observation, interviews, literature study, and documentation. This study indicates that the products offered by Islamic banking can be divided into three major parts, namely products for the distribution of funds (financing), products for raising funds (funding), and service products. Islamic banking has five operational principles, namely the principle of demand deposits, the principle of profit-sharing, the principle of buying and selling and mark-up, the principle of the lease, and the principle of services (fees).Keywords: Products; Services; Islamic Banking  AbstrakBank syariah yaitu bank yang dalam aktivitasnya, baik penghimpunan dana maupun dalam rangka penyaluran dananya memberikan dan mengenakan imbalan atas dasar prinsip syariah yaitu jual beli dan bagi hasil. Tujuan penelitian ini adalah untuk mengetahui bagaimana produk-produk dan jasa dalam perbankan syariah dan bagaimana prinsip-prinsip operasional perbankan syariah. Penelitian ini menggunakan metode survei deskriptif dengan analisis data secara kualitatif. Teknik pengumpulan data yang digunakan yaitu dengan metode observasi, wawancara, studi kepustakaan, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa produk yang ditawarkan oleh perbankan syariah dapat dibagi menjadi tiga bagian besar, yaitu produk penyaluran dana (financing), produk penghimpunan dana (funding), produk jasa (service). Perbankan syariah mempunyai lima prinsip operasional, yaitu prinsip simpanan giro, prinsip bagi hasil, prinsip jual beli dan mark-up, prinsip sewa, dan prinsip jasa (fee).Kata Kunci: Produk; Jasa; Perbankan Syariah